Russia's scalable soft power: leveraging defense diplomacy through the transfer of S-400 triumph. Issue 4 (2nd October 2021) - Arduino, Alessandro; Shuja, Asif
ABSTRACT: Military hardware and technology transfer is increasingly becoming a crucial factor in international relations. This is especially so when the military hardware transfer involves sophisticated weapon's platforms that need specialised training and maintenance, resulting in a long-term relationship that strengthens the geopolitical relationship between the contracting parties. Driven by the re-emergence of great power rivalry, the S-400 Triumph air defence missile system deployment appears to be fast becoming a core component of Russia's military diplomacy. The agreed S-400 export contracts include Turkey, China and India with a long list of interested Middle Eastern countries. The transfer of S-400 well encompasses all the dimensions of the Russian defense diplomacy and could be considered as a primary example of scalable soft power, as it underlines the evolving pattern of high-technology arms transfers that is going to be constant in an increasingly complex multilateral world.